Novel Long-Acting Progesterone Protocols Used to Successfully Synchronize Donor and Recipient Mares With Satisfactory Pregnancy and Pregnancy Loss Rates - Greco, Gabriel M. [UNESP]; Fioratti, Eduardo G. [UNESP]; Segabinazzi, Lorenzo G. [UNESP]; Dell'Aqua, José A. [UNESP]; Crespilho, André M.; Castro-Chaves, Maria Manoela B. [UNESP]; Alvarenga, Marco Antonio [UNESP] (Elsevier, 2016)
The present study aimed to evaluate pregnancy and pregnancy loss rates of recipients treated with alternative long-acting progesterone protocols, designed to synchronize acyclic and cyclic mares, regardless of their cycle phase. A total of 150 Campolina breed mares were used as recipients. Recipient mares were assigned to six different groups with 25 animals each. Groups 1 to 5 were treated with progesterone at some point. Group 1 (acyclic recipients); group 2 (cyclic estrous recipients with one ≥35 mm follicle); group 3 (cyclic estrous recipients with an anovulatory follicle); group 4 (early estrous cyclic recipients); group 5 (diestrous cyclic recipients), and group 6 (cyclic recipients-control). Embryos (day 8) were transferred 4 days after ovulation or 4 days after progesterone injection. Pregnant diagnosis was performed by transrectal ultrasonography 1 week after embryo transfer. Pregnant recipients were evaluated for possible losses and mares treated every 14 days with 3 g (intramuscular) of long-acting progesterone, until 120 days of pregnancy. Pregnancy at 15 days and pregnancy loss rates were recorded and statistically evaluated through multivariate regression (P < .05). Pregnancy and pregnancy loss rates were similar within groups (G1: 76%-10.5%; G2: 76%-5.9%; G3: 56%-0%; G4: 80%-10%; G5: 60.9%-0%; and G6: 60%-13.3%). In conclusion, the novel long-acting progesterone protocols proposed in this study allowed successfully the utilization of mares with asynchronous cyclic as embryo recipients, serving as an alternative specially when few recipients are available and usual synchronization is not possible.
Keywords: Embryo transfer; Progesterone protocol; Recipient mare